A web service for farming management - Kok, Zhi Xin (2024)
This project is a web service project with a farming industry focus. It aims to assist the farmers for better handling of their farms by exchanging information between other farmers, agricultural equipment vendors as well as customers. In the interim, it aims to maximize the profitability by providing a channel for the direct communication or deal in agricultural communities and marketplace. Through this way, it provides farmers with the opportunity to boost their profitability. Standard HTML, CSS, and JavaScript were used throughout the entire web project’s development to create the frontend, and PHP and MySQL were used to create the backend. Simply put, the graphical user interface will leverage the strength of standard HTML, CSS, and JavaScript, which offers a clear user interaction. It is recognized that using an effective GUI on a web project that enables users to use the web service comfortably makes it possible to communicate clearly. The power of PHP and MySQL will serve as the web project's back end throughout all phases of development. Simply put, the SQL queries will be embedded using the PHP language, allowing for the retrieval, and updating of data from MySQL once embedded. In a brief, PHP is used to connect the front end and back end. In terms of hardware, a laptop running Windows 11 will be used for the timeframe of the web project's development. Additionally, Agile Methodology [10] will be used in situations where it is more adaptable to changes or add new functionalities over the course of a web project's development. By utilizing these methods or languages, it will be possible to create a web service for managing farms that is perfect and fully functional while also making it user-friendly.